The Butterfly Complex [{Cp*Cr(CO)(3)}(2)(μ,η(1:1)‐P(4))] as a Versatile Ligand and Its Unexpected P(1)/P(3) Fragmentation - Grünbauer, Rebecca (Chemistry, 2020)
The versatile coordination behavior of the P(4) butterfly complex [{Cp*Cr(CO)(3)}(2)(μ,η(1:1)‐P(4))] (1) towards Lewis acidic pentacarbonyl compounds of Cr, Mo and W is reported. The reaction of 1 with [W(CO)(4)(nbd)] (nbd=norbornadiene) yields the complex [{Cp*Cr(CO)(3)}(2)(μ(3),η(1:1:1:1)‐P(4)){W(CO)(4)}] (2) in which 1 serves as a chelating P(4) butterfly ligand. In contrast, reactions of 1 with [M(CO)(4)(nbd)] (M=Cr (a), Mo (b)) result in the step‐wise formation of [{Cp*Cr(CO)(2)}(2)(μ(3),η(3:1:1)‐P(4)){M(CO)(5)}] (3 a,b) and [{Cp*Cr(CO)(2)}(2)‐(μ(4),η(3:1:1:1)‐P(4)){M(CO)(5)}(2)] (4 a,b) which contain a folded cyclo‐P(4) unit. Complex 4 a undergoes an unprecedented P(1)/P(3)‐fragmentation yielding the cyclo‐P(3) complex [Cp*Cr(CO)(2)(η(3)‐P(3))] (5) and the as yet unknown phosphinidene complex [Cp*Cr(CO)(2){Cr(CO)(5)}(2)(μ(3)‐P)] (6). The identity of 6 is confirmed by spectroscopic methods and by the in situ formation of [{Cp*Cr(CO)(2)(tBuNC)}P{Cr(CO)(5)}(2)(tBuNC)] (7). DFT calculations throw light on the bonding situation of the reported products.